Developing your portfolio enhancing your learning and showing your stuff : a guide for the early childhood student or professional - Jones, Marianne (Marianne E.); Shelton, Marilyn (Marilyn R.). (New York Routledge, 2011)
"Portfolios aren?t just for documenting the work of young children--they can also be powerful resources for early childhood educators? professional preparation and development, from evaluating one?s classroom practice to showcasing skills and accomplishments. Veteran teacher educators Marianne Jones and Marilyn Shelton provide practical and comprehensive guidance on developing a portfolio specific to the needs of pre- and in-service teachers of young children. This updated new edition features: - A flexible and friendly approach that guides students at varying levels of experience through the portfolio process. - New material on portfolio planning and organization and additional coverage on writing rationales and captions - A companion website with additional instructor and student resources such as guides for activities, PowerPoint slides, printable templates, questions to ponder, and worksheets for improving students? portfolio skills. Both theoretical and practical, this valuable resource addresses issues and mechanics related to process and product, instruction and guidance techniques, the role of reflection, and assessment strategies. With concrete examples, rubrics, tips, and exercises, this book provides a step-by-step guide to creating a professional teaching portfolio"--Provided by publisher.
Human development and constructivism -- How portfolios reflect constructivism -- Portfolio orientation : purpose, type, context, structure, and audience -- Planning and organizing for a successful portfolio -- Philosophy : the unifying element of portfolios -- Reflection : the defining feature of portfolios -- Building a portfolio -- Structure, design, and construction of print and electronic portfolios.
Keywords: Portfolios in education; Early childhood teachers -- Training of